Derepression of Mineral Phosphate Solubilization Phenotype by Insertional Inactivation of iclR in Klebsiella pneumoniae. - Mahendrapal Singh Rajput; Bhagya Iyer; Maharshi Pandya; Rahul Jog; Naresh Kumar G; Shalini Rajkumar (PLoS ONE, 2015)
The mode of succinate mediated repression of mineral phosphate solubilization and the role of repressor in suppressing phosphate solubilization phenotype of two free-living nitrogen fixing Klebsiella pneumoniae strains was studied. Organic acid mediated mineral phosphate solubilization phenotype of oxalic acid producing Klebsiella pneumoniae SM6 and SM11 were transcriptionally repressed by IclR in presence of succinate as carbon source. Oxalic acid production and expression of genes of the glyoxylate shunt (aceBAK) was found only in glucose but not in succinate- and glucose+succinate-grown cells. IclR, repressor of aceBAK operon, was inactivated using an allelic exchange system resulting in derepressed mineral phosphate solubilization phenotype through constitutive expression of the glyoxylate shunt. Insertional inactivation of iclR resulted in increased activity of the glyoxylate shunt enzymes even in succinate-grown cells. An augmented phosphate solubilization up to 54 and 59% soluble phosphate release was attained in glucose+succinate-grown SM6Δ and SM11Δ strains respectively, compared to glucose-grown cells, whereas phosphate solubilization was absent or negligible in wildtype cells grown in glucose+succinate. Both wildtype and iclR deletion strains showed similar indole-3-acetic acid production. Wheat seeds inoculated with wildtype SM6 and SM11 improved both root and shoot length by 1.2 fold. However, iclR deletion SM6Δ and SM11Δ strains increased root and shoot length by 1.5 and 1.4 folds, respectively, compared to uninoculated controls. The repressor inactivated phosphate solubilizers better served the purpose of constitutive phosphate solubilization in pot experiments, where presence of other carbon sources (e.g., succinate) might repress mineral phosphate solubilization phenotype of wildtype strains.